PENGARUH DISIPLIN BELAJAR DAN VARIASI MENGAJAR GURU TERHADAP HASIL BELAJAR PADA MATA PELAJARAN IPS SISWA KELAS IX SMP NEGERI 1 TAPIAN DOLOK - Adriana Natasha Pandiangan; Binsar Tison Gultom; Debbi Petra Meyana Sitorus (JOURNAL SAINS STUDENT RESEARCH, 2024)
discipline and teacher teaching variations on learning outcomes in social studies subjects for grade IX students at SMP Negeri 1 Tapian Dolok.This type of research is descriptive quantitative research with a study population of 112 grade IX students at SMP Negeri 1 Tapian Dolok, and the sample used is all students who are part of the population. The sampling technique used is Non sampling The sampling technique used is non-sampling. Data collection techniques are carried out through observation and questionnaires (questionnaires). The hypothesis data collection technique uses multiple regression analysis, a partial test (t), a simultaneous test (f), and a coefficient of determination (R2).The results stated that: 1) There is a positive and significant influence of learning discipline on student learning outcomes, as seen from the t test, where the calculated value of learning discipline (4.596) > the ttable value (1.981). 2) There is a positive influence of teacher teaching variation on student learning outcomes: This result is seen in the t test, where the calculated value of teacher teaching variation (2.508) > ttable, (1.981), which means that the variable has an effect. 3) Learning discipline and teacher teaching variations together affect learning outcomes, these results can be seen in the F test, where the Fcalculate value (67.432) > the Ftable value (3.08). The R squared coefficient of determination test is known to be 0.553, which means 55.3% of learning discipline variables and teacher teaching variations affect learning outcomes in social studies subjects of grade IX students of SMP Negeri 1 Tapian Dolok. While 44.7% is the influence of other variables that were not studied in this study.Based on the results of the study, it can be concluded that the learning discipline and teaching variations of teachers have a significant effect on the learning outcomes in social studies subjects of grade IX students of SMP Negeri 1 Tapian Dolok.